The Right to Access to Information for Users with Special Needs and Disabilities - Boras, Damir (Array, 2004)
In the information society the right to access to information is a must. Ensuring equal access to information for all is one of library s missions. People with special needs and disabilities make between 15 and 25 % of the population in world s countries. The majority of this group of people are not library users because libraries do not ensure services adapted to their special needs. Many of them need assistive technologies to access information. The advance of the digital information and the Internet together with the development of more and more sophisticated assistive technologies has helped promote these issues more than ever before. For example, blind and visually impaired people do not need to wait for a book to be produced in Braille, which is a very slow and expensive process. Less than 15 % of the published books per year in some of the most developed countries of the world ever make into Braille. The digital information can easily be accessible via speech synthesis software, which reads aloud everything that is on the computer screen. Projects in several countries of the world have been started with the aim of building digital collections of materials accessible to people with disabilities. A closely related issue is that of copyright, as the digital information is more easily distributed than paper. The digital form is also readable by all, unlike Braille. People with special needs have higher life expenses in general and thus according to international recommendations transferring to another format should be considered as fair use. However, exemption to copyright for people with special needs and disabilities has been regulated in few countries. In Croatia, a Digital collection for students with special needs and disabilities has been created at the Faculty of Philosophy, University of Zagreb in cooperation with the Croatian Association for the Blind. For each publication a contract with copyright owners needs to be signed. A new draft of copyright law is being composed, which will hopefully include an exemption for people with special needs and disabilities and thus create an opportunity for making a step further towards the democratic information society. Ensuring and organising access to educational materials in the electronic environment is an important factor in determining realistic requests for development and advancement of education. If we want to participate in European processes and knowledge society, then ensuring access to educational materials across the telecommunications flow is the part in which we need to participate with solutions of our own. In the paper the authors will concentrate on organising and presenting knowledge and information in the electronic environment, on the level of postsecondary education. The context of IT is dealt from the perspective of achieving free access to information and knowledge and providing information for all. This altogether involves planning and creating repository of educational materials, their description and indexing while implementing current metadata standards, attitude analysis of both teaching staff and students, as well as taking into consideration the concept of freedom of access to information versus copyright protection.